PacBio Isoform Sequencing and Illumina RNA Sequencing Provide Novel Insights on Responses to Acute Heat Stress in Apostichopus japonicus Coelomocytes - Wang, Yanlin; Yin, Yingchao; Cong, Xiao; Storey, Kenneth B.; Chen, Muyan (Frontiers in Marine Science, 2022)
Significant increases in global sea surface temperatures are expected with climate change and may cause a serious challenge for marine organisms cultured in aquatic environments that are characterized by short and long-term fluctuations in water temperatures. Apostichopus japonicus, a sea cucumber with high nutritional value and pharmacological properties, is an important economic species that is widely raised in aquaculture in China. In recent years, continuous extreme high temperatures (up to 30°C) have occurred frequently in summer leading to mass mortality of sea cucumbers cultured in semi-open shallow regions seriously restricting the sustainable development of sea cucumber aquaculture. In the present study, we combined RNA-seq and PacBio single-molecular real-time (SMRT) sequencing technology to unveil the potential mechanisms of response to acute heat stress in A. japonicus coelomocytes. A total of 1,375 differentially expressed genes (DEGs) were identified in a comparison of control and 48 h heat stress (HS) groups. Pathway enrichment analysis indicated that nine important pathways induced by HS were significantly enriched (q-value < 0.05) and mostly fell into four classes: folding, sorting, and degradation, immune and infectious diseases, signal transduction, and post-transcriptional regulation. Among them, all 41 genes connected with protein processing in endoplasmic reticulum were significantly up-regulated, and 12 of these were selected and validated via qPCR. Furthermore, changes in alternative splicing (AS) were also identified in sea cucumbers following HS. A total of 1,224 and 1,251 differential alternative splicing (DAS) events were identified using splice junction counts (JC only) and reads on target and junction counts (JCEC) as the input for rMATS in CO-HS comparison. We further found that the RNA splicing-related genes were enriched in the spliceosome pathway and showed DAS in control versus heat-stressed animals. In particular, we compared and confirmed that the hsfs1 gene, the master regulator of the heat shock response, showed differentially spliced exons in response to HS. This is the first comprehensive study showing that transcriptional and post-transcriptional (AS) controls are involved in the acute heat stress response of sea cucumber coelomocytes and provides novel insights into the molecular mechanisms of echinoderm adaptation to environmental stress.